PERFECŢIONAREA SISTEMULUI MOTIVAŢIONAL ÎN ÎNTREPRINDERILE MICI ŞI MIJLOCII - Mironov, Svetlana (CEP USM, 2007)
Motivation is a process of stimulating the worker during his/her activity, aimed at achieving the organization's objectives. Motivation is important for the productive fulfillment of decisions taken and works projected
Keywords: managementul firmei; întreprinderi mici; managementul resurselor umane